Awareness and Readiness of Fire Officers on The Possession of Firearms: Basis for Policy Development - Cruz, Quennie Villare (Future Science / FSH-PH Publications, 2024)
Republic Act No. 11589, known as the Bureau of Fire Protection Modernization Act of 2021, aims to enhance the Bureau of Fire Protection (BFP) in the Philippines by improving firefighters' ca-pabilities in fire prevention, suppression, investigation, and emer-gency medical services. The law also authorizes the issuance of firearms to certain firefighters to ensure their safety and that of their colleagues while performing their duties. This study used a descriptive-correlational research design and quantitative meth-ods to assess BFP fire officers' awareness and readiness regarding firearm possession, bearing, and carrying. Data were collected from 120 respondents at the Caloocan City Fire Station between November 15 and 28, 2023. The findings indicate that fire officers generally understand firearm laws and procedures well, including licensing requirements such as age limits and background checks, though they encounter challenges with paperwork and license re-newals. They are also familiar with the rules for carrying firearms, including permit requirements and concealment during duty. The results highlight the need for enhanced training and clearer regula-tions to ensure safe firearm use and minimize incidents, in line with broader research on firearm policies and education. The study concludes that, despite a solid understanding of firearm reg-ulations, there is a need for improved licensing processes and training. Recommendations include developing comprehensive and practical training programs, conducting regular refresher courses, creating accessible reference materials, and improving licensing procedures through flexible scheduling and simplified paperwork, as well as addressing training challenges through bet-ter recruitment, funding, and facilities.